The Shortage of Consciousness in Adolescents Performing Congregational Prayers at Mosque - Supriadi, Dedi; Mujahidin, Endin; Bahagia, Bahagia (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Mosque in Cigola Village. This study focuses on the problems of teenagers in Cigola Village, namely why these teenagers do not pray in congregation at the Al-Barokah Mosque. In modern times, this is one of the factors that teenagers do not pray in congregation to the mosque, because they are busy surfing in cyberspace (social media), playing games, and so on, causing a feeling of laziness, thus there is a lack of awareness of teenagers to pray in congregation at the mosque. . In this study, we use a qualitative approach that aims to describe the lack of awareness of teenagers to pray together at the Al-Barokah Mosque in Cigola Village. We collected this research data by means of online interviews and observation. As for the results of our research, it is true that there are many teenagers who do not participate in congregational prayers at Majid Al-Barokah, the majority of mosque congregations are filled by parents. This proves that there is indeed a lack of awareness for teenagers to pray in congregation at the mosque.